Gender differences in Body Mass Index and physical activity of students of the University of Tuzla - Atikovic Almir; Hodzic Sanjin; Bilalic Jasmin; Mehinovic Jasmin; Mujanovic Amra Nozinovic; Mujanovic Edin; Kapidzic Alen (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2014)
Background: This study was carried out among undergraduate students at the University of Tuzla (Bosna and Herzegovina) with the objective of examining gender differences in the body mass index (BMI) and the level of Physical Activity (PA) among respondents.